B28 The external oblique intercostal plane block as part of enhanced recovery after pancreatic surgery: a case series. (11th August 2022) - Liotiri, D; Diamantis, A; Sioka, E; Vassia, G; Stamatiou, G; Zacharoulis, D
Abstract : Background and Aims: With informed consent, we report our clinical experience with External Oblique Intercostal (EOI) block for a series of four patients who underwent pancreatoduodenectomy. All four patients had their pain well controlled under Thoracic Epidural Analgesia (TEA) for the first 72 hours. When the epidural catheter removed, we sited bilateral EOI catheters as part of a step-down multimodal analgesia approach. EOI block is a recently described fascial plane block which covers the anterior and lateral upper abdominal wall. 1 Methods: We injected a bolus of 20 ml Ropivacaine 0.375% via each catheter twice a day for the first 48 hours and then once a day for the next 48 hours. We removed the catheters after four days. All patients received Paracetamol 1gr every 8 hours and Gabapentin 300mg at bedtime. Results: All patients remained pain and opioid free and able to mobilise and breath effectively. All patients were very satisfied with analgesia provided by the EOI catheters. Conclusions: With the evolution of regional anaesthesia techniques, the opioid use in acute pain management needs to be re-evaluated. 2 We used the EOI block to provide enhanced recovery analgesia 3 for pancreatoduodenectomy. We have shown that a regional block could be used for step-down analgesia to avoid opioid use and improve outcomes.